Pengembangan program psikoedukasi untuk mengelola stres, cemas, dan depresi pada mahasiswa yang sedang menempuh skripsi - Zainul Anwar; Djudiyah Djudiyah (Fakultas Psikologi, 2021)
Some students, working on a thesis is a ”scourge” because they have to do it themselves and interact personally with other people. This is where students sometimes feel depressed, anxious, and depressed because of the various problems they face. One of the strategies used is to provide psychoeducation programs that are relevant to the problem. The research objective is to find a problem and a psychoeducation model for that problem. The research method used is descriptive quantitative, the subject was taken purposively as many as 63 respondents and descriptive analysis. The results found includes: (a) The main problems are communication with supervisors, self-management and time, looking for references, low motivation, writing a thesis according to APA Style, and economic and family issues, and (b) Psychoeducation program model with achievement motivation training material, persuasive communication training, training program applications quotes, and especially for those who need special treatment, the counseling or psychotherapy process is carried out individually.